Pengembangan Multimedia Pembelajaran pada Materi Sistem Ekskresi Manusia Mata Pelajaran IPA Kelas VIII SMP (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop multimedia learning that can help students to understand the process of the human excretory system and can facilitate students to learn independently. This type of research is research and development (R&D) with a 4-D development model. The results of the study obtained that the average validity score by material experts was 4.85 with the category of "very valid"." The average validity score from validator 1 is 4.88, also categorized as "very valid," while the average score from validator 2 is 4.79, categorized as "very valid." Subsequently, a practicality test was conducted with 20 students, resulting in a score of 4.62, categorized as "very practical." Based on the practicality test results, it is concluded that the learning multimedia on the topic of the human excretory system for eighth-grade science subjects can be used in the teaching and learning process.